New or interesting Pyraloidea for the European and Italian faunas (Insecta: Lepidoptera) - Graziano Bassi; Friedmar Graf; Frantisek Slamka (SHILAP, 2025)
New data on European Pyraloidea are shown following the study of material present in the authors’ collections as well as well as in the Natural History Museum of Denmark (Copenhagen). Catoptria plitvicensis Bassi, sp. nov. and Catoptria velebitica Bassi, sp. nov. from Croatia, and Melathrix edmundsi Slamka, sp. nov. from Crete are described. Arsissa firusella (Amsel, 1961) (Pyralidae: Phycitinae), Euchromius subcambridgei Bleszynski, 1965 (Crambidae: Crambinae) and Crocidophora tuberculalis Lederer, 1863 (Crambidae: Pyraustinae) are new for Europe. Gymnancyla hillneriella Gastón & Vives, 2018, Pempeliella ardosiella (Ragonot, 1887), Pempeliella bulgarica Slamka & Plant, 2016, and Phycita torrenti Agenjo, 1962 (all Pyralidae: Phycitinae) are reported as new for Italy. Calamotropha paludella (Hübner, [1824]) (Crambidae: Crambinae) is reported as new for Sicily, Gymnancyla canella ([Denis & Schiffermüller], 1775) (Pyralidae: Phycitinae) is reported as new for Sardinia and South Italy. Pempelia alpigenella (Duponchel, 1836) (Pyralidae: Phycitinae) is reported as new for Northwestern Italy and Bradyrrhoa gilveolella (Treitschke, 1833) (Pyralidae: Phycitinae) is reported as new for continental Italy.